The neutrophil to lymphocyte ratio (NLR) and the presence of large nodal mass are independent predictors of early response: A subanalysis of the prospective phase II PET‐2‐adapted HD0607 trial. (6th November 2020) - Romano, Alessandra; Pavoni, Chiara; Di Raimondo, Francesco; Tarella, Corrado; Viviani, Simonetta; Rossi, Andrea; Patti, Caterina; Picardi, Marco; Cantonetti, Maria; La Nasa, Giorgio; Trentin, Livio; Bolis, Silvia; et al.
Abstract: Background: The neutrophil to lymphocyte ratio (NLR) and the lymphocyte to monocyte ratio (LMR) can reflect both the myeloid dysfunction and T‐cell immune suppression and have prognostic significance. Methods: In 771 newly diagnosed advanced‐stage Hodgkin Lymphoma (HL) patients we evaluated the baseline values of NLR and LMR as predictors of clinical outcome. According to the multicenter prospective phase II GITIL‐HD0607 trial, all patients received two ABVD courses and if PET‐2 negative received four additional ABVD cycles while if PET‐2‐positive patients were randomized to either BEACOPP escalated (Be) plus BEACOPP baseline (Bb) (4 + 4 courses) or Be + Bb (4 + 4) and Rituximab. PET scans were centrally reviewed by an expert panel by Blinded Independent Central Review. Results: Higher NLR and lower LMR were associated with a PET‐2 positivity and failure to achieve long‐term disease control, respectively. By univariate and multivariate analysis, large nodal mass (>7 cm), IPS ≥ 3, NLR > 6 were strong independent predictors of early PET‐2 response after ABVD. Only NLR > 6 and IPS ≥ 3 were strong independent predictors of outcome at diagnosis; however, when PET‐2 status was added, only PET‐2‐positive status and IPS ≥ 3 were independent predictors of PFS. Focusing on PET‐2‐negative patients, those with NLR > 6 had an inferior 3‐year PFS compared to patients with NLR ≤ 6 (84% vs 89% months, P  = .03). Conclusion: In advanced‐stage HL patients treated with a PET‐2‐driven strategy, IPS ≥ 3 and NLR > 6 are independent predictors of outcome at diagnosis while the presence of large nodal mass, IPS ≥ 3, and NLR > 6 at diagnosis are independent predictors of early ABVD response. Abstract : In the setting of newly diagnosed advanced‐stage HL patients, the presence of large nodal mass, IPS ≥ 3, and NLR > 6 at diagnosis are independent predictors of early ABVD response. IPS ≥ 3 and NLR > 6 are also useful predictors of outcome in PET‐2‐negative patients.